2021
DOI: 10.2478/bjmg-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously both expression of LMP-1 and methylation of E-cadherin: Molecular biomarker in stage IV of nasopharyngeal carcinoma patients

Abstract: The phenome of E-cadherin gene methylation and the expression of latent membrane protein 1 (LMP-1) gene are associated with nasopharyngeal carcinoma (NPC). In order to determine whether cooperative LMP-1 expression or methylation of E-cadherin could serve as the potential molecule biomarker target for diagnosis and therapy of NPC, a case-control study including 93 NPC biopsy samples and 100 non cancerous nasopharyngeal swab samples were examined, as well as the strength of association among them by the quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Events of epigenetics, one of the genetic disorders, have been reported that plays striking roles in many human cancers, including NPC (Herceg & Hainaut, 2007;Dai, Zheng, Cheung, & Lung, 2016;. DNA hypermethylation (or DNA methylation) is the best-studied epigenetic alteration (Herceg & Hainaut, 2007;Lao, Truong, et al, 2021). The DNA methylation refers to the transfer a methyl group from S-adenyl methionine to the bases of 5-carbon of Cytosine which is located at 5' to a Guanosine base in a CpG dinucleotide by DNA methyltransferase (DNMT) (Herceg & Hainaut, 2007;Moore, Le, & Fan, 2013;Lao, Truong, et al, 2021) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Events of epigenetics, one of the genetic disorders, have been reported that plays striking roles in many human cancers, including NPC (Herceg & Hainaut, 2007;Dai, Zheng, Cheung, & Lung, 2016;. DNA hypermethylation (or DNA methylation) is the best-studied epigenetic alteration (Herceg & Hainaut, 2007;Lao, Truong, et al, 2021). The DNA methylation refers to the transfer a methyl group from S-adenyl methionine to the bases of 5-carbon of Cytosine which is located at 5' to a Guanosine base in a CpG dinucleotide by DNA methyltransferase (DNMT) (Herceg & Hainaut, 2007;Moore, Le, & Fan, 2013;Lao, Truong, et al, 2021) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…DNA hypermethylation (or DNA methylation) is the best-studied epigenetic alteration (Herceg & Hainaut, 2007;Lao, Truong, et al, 2021). The DNA methylation refers to the transfer a methyl group from S-adenyl methionine to the bases of 5-carbon of Cytosine which is located at 5' to a Guanosine base in a CpG dinucleotide by DNA methyltransferase (DNMT) (Herceg & Hainaut, 2007;Moore, Le, & Fan, 2013;Lao, Truong, et al, 2021) (Figure 1). Importantly, aberrant methylation of DNA is significantly related to a wide variety of human cancers, including NPC (Herceg & Hainaut, 2007;Dai et al, 2016;Lao, Truong, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations